Mediation and Agreement of Forestry Cooperation as a Conflict Settlement of PT Bumi Mekar Hijau Production Forest Area With Community of Riding Village - Miran Suhardi; Zulfikri Suleman; Azwardi Azwardi (Program Pascasarjana Universitas Sriwijaya, 2019)
Conflicts in forest areas usually occur due to unclear rights or laws relating to the tenure system. This can happen between individuals, communities, government agencies or private sector. The boundaries of forest areas that have not been agreed upon by the community and the government also trigger conflict. The reality in the field shows that the land in the forest area has been used by the community or the surrounding population, both migrants and local residents, but the existence of these communities has not been accommodated, especially in forestry development planning. The development of industrial timber plantations (in Indonesian – “hutan tanaman industri”, HTI) and plantations on a large scale has different backgrounds. The development of industrial plantations (HTI) is motivated more by the emergence of a large number of unproductive production forests and incentives that attract the private sector. Government policies concerning forest conversion and land use as well as various investment ease packages encourage growth in the sector's development. This study aims to determine the dynamics of the conflict, and the mediation of forestry cooperation agreements as a process of resolving the conflict of production forest area holders of PT Bumi Mekar Hijau's license and Riding Village community in Pangkalan Lampam sub-district, Ogan Komering Ilir Regency. This study uses a method qualitative research with descriptive data presentation. Qualitative methods in this study are defined as research procedures that produce description data in the form of written or oral words from people and observed behavior. The aim is to explain the phenomena of collecting data in depth. The population and sampling in qualitative research are very limited. With population limitations and sampling, the data collected must be in-depth and can explain the phenomenon under study. Here more emphasized is the issue of the depth of data quality. Data analysis was carried out by means of an inherent analysis of each aspect of the forest concession conflict case found. The analysis is also based on the existing conflict themes in accordance with the results of the interpretation of the cases found. In this case, the analysis process can take place since the data collection process is carried out. By state law, the area is part of the business license for utilization of plantations in industrial plantations (IUPHHK-HTI) PT. Bumi Mekar Hijau. But at that time, the company opened production forests in the region. The new activity is only canal digging and land clearing. The Riding Village Dusun I and II occupied an area of around 10,000 hectares because they felt that the company and the government had never asked their permission to make land an industrial plantation. The community has evidence that the land belongs to their ancestors, namely “sonor” (planting rice) and trenches for timber by their ancestors in the region. This physical evidence is a source of community power to survive claiming the area. In July 2013, the people of Riding Village and PT. Bumi Mekar Hijau agreed to resolve land conflicts through an open, concrete and successful dialogue process. Both parties appointed Wahana Bumi Hijau (WBH) and Imparsial Mediator Networking (IMN) as mediators who assisted the negotiation process. Since the mediation process has taken place it has been very difficult for both parties to agree on what was delivered and there is no point of completion. But on March 16, 2017 the MoU on conflict peace in Desa Riding with PT. Bumi Mekar Hijau was held at the Forestry Service of South Sumatra Province which was attended by the Village Government and Riding community, Tripika Sub-District Pangkalan Lampam, IMN Mediator, Asia Pulp and Paper (APP), Forest Service District Ogan Komering Ilir District, South Sumatra Provincial Forestry Service, Directorate of handling tenure and customary forest conflicts and Director of Sustainable Production Forest Management. On April 21, 2017, the signing of a forestry cooperation agreement between PT. Bumi Mekar Hijau with Riding Village was held, in Riding Village with an area of 10,000 hectares, which was intended for 3,500 hectares of acacia plant partnerships, 1500 hectares of wana tani (Agroforestry) partnerships, 610 hectares for drainage infrastructure, 333.6 hectares for residential settlements, 1,000.8 hectares for government-owned road infrastructure, 1,863.4 hectares of forage buffalo land and 1,192.2 hectares of protected area.